Performance Pay, Risk Attitudes and Job Satisfaction - Thomas Cornelißen; John S. Heywood; Uwe Jirjahn (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We present a sorting model in which workers with greater ability and greater risk tolerance move into performance pay jobs and contrast it with the classic agency model of performance pay. Estimates from the German Socio-Economic Panel confirm testable implications drawn from our sorting model. First, prior to controlling for earnings, workers in performance pay jobs have higher job satisfaction, a proxy for on-the-job utility. Second, after controlling for the higher earnings associated with performance pay, the job satisfaction of those in performance pay jobs is the same as those not in such jobs. Third, those workers in performance pay jobs who have greater risk tolerance routinely report greater job satisfaction. While these findings support the sorting model, they would not be suggested by the classic agency model.
Keywords: D80; J24; J28; J33; M52; 330; Performance Pay; Worker Heterogeneity; Ability; Risk Preferences; Sorting